Learning Tableau 2020 : create effective data visualizations, build interactive visual analytics, and transform your organization - Milligan, Joshua N (Packt Publishing Ltd, Birmingham, Uk., 2020)
This comprehensive Tableau guide equips you with the skills to effectively leverage its powerful features for data analysis and visualization. From foundational principles to advanced techniques, the book covers a wide range of topics, including data connections, visualizations, calculations, LOD expressions, dashboards, and storytelling. By the end, you'll be able to create stunning visuals, connect to various data sources, clean and structure data using Tableau Prep, and make informed decisions based on your data insights.
Includes index.
Keywords: Tableau fundamentals; Data connections and preparation; Visualizations and storytelling